Motivation Problematics of Arabic Learners During Covid-19 Pandemic l Al-Musykilat al-Dafiiyyah lada Muta’allimi al-Lugah al- ‘Arabiyyah Tiwala Jaikhah Covid-19 - Marwa, Atikah; Al Nabiil, Ach. Rifqiy; Syuhadak, Syuhadak (Universitas Islam Negeri Raden Intan Lampung, 2021)
Motivation is one of the aspects of psychology that can affect the effectiveness of learning, especially in learning Arabic as a foreign language. In this study, motivation was a major concern in Arabic language learning, especially in Islamic High School in Malang. Hence, to reveal and provide solutions to this problem, this research was conducted with a qualitative approach, the data source was obtained from observations and interviews with students, and supported by several documents. The results of this study indicated the motivation problems experienced by Islamic high school students in Malang were economic factors, low parenting education, low self-esteem of students, low linguistic attitudes, lack of interesting teaching materials and lack of understanding of Arabic importance. This result was in accordance with the motivation theory according to Fauzi and Helen which related to the internal and external aspects of the learner. This research had implications for Arabic learning which was based on the learner's motivation which is influenced by factors. Eventually, it could become the literature and reference which related to the motivation problems in language learning, especially Arabic.